Thermal properties of polyethylene reinforced with recycled– poly (ethylene terephthalate) flakes - Nik Ruqiyah, Nik Hassan; Noor Mazni, Ismail; Suriati, Ghazali; Nuruzzaman, D. M. (IOP Publishing Ltd, 2018)
In this study, recycled plastic bottles (RPET) were used as a filler in high density polyethylene (HDPE) thermoplastic. The plastic sheet of RPET/HDPE was prepared by using hot and cold press machine. The effects of RPET addition and hot press process to the thermal properties of the composite RPET/HDPE were investigated using differential scanning calorimetry (DSC) and thermogravimetric (TGA). Results from DSC analysis show that the melting point of HDPE slightly shifted to a higher temperature for about 2°C to 4°C with the addition of RPET as a filler. The starting degradation temperature of RPET/HDPE composite examined from TGA analysis also seen to be slightly increased. It was observed that the incorporation of recycled PET flakes into HDPE is achievable using hot press process with slight improvement seen in both melting point and thermal stability of the composite compared to the neat HDPE.